A Comparative Study of Atracurium and Cisatracurium for Assessment of Intubating Conditions - Pooja Shah; Rahul Chalekar (Academia Anesthesiologica International, 2020)
Background: The present study was conducted to compare atracurium and cisatracurium for the assessment of intubating conditions. Subjects and Methods: 60 patients of the American Society of anaesthesiology (ASA) class I and II between the age group of 20-60 years were randomly divided into 2 groups of 30 each. Group I received atracurium in the dose of 0.5 mg/kg body weight and group II patients received cis-atracurium in the dose of 0.2 mg/kg body weight. Parameters such as arterial blood pressure, heart rate and onset time and duration of action were recorded. Results: The mean onset of action in group I was 3.4 minutes and in group II was 2.6 minutes. The mean duration of action in group I was 36.2 minutes and in group, II was 64.1 minutes. The mean heart rate was 98.2 beats/min, 96.1 beats/mins and 109.3 beats/mins at baseline, after injection of muscle relaxant and after the attempt of intubation respectively in group I. In group II was 93.5 beats/min, 98.5 beats/min and 97.4 beats/min respectively in group II. The mean arterial pressure was 89.6 mmHg, 93.7 mmHg and 98.5 mmHg at baseline, after injection of muscle relaxant and after the attempt of intubation respectively in group I. In group II was 90.4 mmHg, 92.5 mmHg and 94.1 mmHg respectively in group II. The difference was significant (P< 0.05). Conclusion: Cisatracurium is more efficacious as compared to atracurium with respect to intubating conditions.